The Locking Y Lateral Canthopexy With Osseous Integration: Clinical Experience and Surgical Technique. Issue 5 (September 2016) - Kossler, Andrea L.; Erickson, Benjamin P.; Shriver, Erin M.; Tse, David T.
Abstract : Purpose: To describe a surgical technique to correct lateral canthal tendon disinsertion with a strabismus surgery-inspired locking capture of the tendon complex and osseous integration via drill holes. Methods: Retrospective interventional case series including all patients with lateral canthal tendon disinsertion who underwent locking Y lateral canthopexy with drill hole reinforcement by 1 surgeon (D.T.T.) between 2006 and 2011. Outcome measures included resolution of presenting ocular symptoms, improved blink dynamics and lid closure, correction of lagophthalmos and exposure keratopathy, and need for further surgery. Results: A total of 53 lateral canthopexies with osseous integration were performed in 42 patients who fulfilled clinical criteria for lateral canthal tendon disinsertion. The population was biased toward treatment failures; 81% of eyes (43/53) had a history of prior lateral canthal tightening, and of these 30.2% (16/53) had undergone 3 or more procedures. Postoperatively, all eyes demonstrated improved eyelid position and blink mechanics, and 83% (44/53) had subjective resolution of epiphora and ocular irritation. Lagophthalmos was fully corrected in 95% (19/20) of cases, and corneal staining resolved in 88% (14/16). With a mean follow-up period of 24 months, 3.7% of eyes (2/53) required additional lateral canthal tightening. Conclusions: The locking Y lateral canthopexy is an effective and durable method for repositioning the lateral canthal tendon complex to improve blink dynamics, eyelid closure, and cosmesis. Even in a population heavily biased toward treatment failure, clinical results are excellent and the reoperation rate is low. Abstract : The locking Y lateral canthopexy with osseous integration is an effective and durable method for repositioning the lateral canthal tendon complex to improve blink dynamics, eyelid closure, and cosmesis.